Adapting to Climate Change in Eastern Europe and Central Asia - Fay, Marianne; Block, Rachel I.; Ebinger, Jane (World Bank, 2012)
The climate is changing, and the Eastern Europe and Central Asia (ECA) region is vulnerable to the consequences. Many of the region's countries are facing warmer temperatures, a changing hydrology, and more extremes, droughts, floods, heat waves, windstorms, and forest fires. This book presents an overview of what adaptation to climate change might mean for Eastern Europe and Central Asia. It starts with a discussion of emerging best-practice adaptation planning around the world and a review of the latest climate projections. It then discusses possible actions to improve resilience organized around impacts on health, natural resources (water, biodiversity, and the coastal environment), the 'unbuilt' environment (agriculture and forestry), and the built environment (infrastructure and housing). The last chapter concludes with a discussion of two areas in great need of strengthening given the changing climate: disaster preparedness and hydro-meteorological services. This book has four key messages: a) contrary to popular perception, Eastern Europe and Central Asia face significant threats from climate change, with a number of the most serious risks already in evidence; b) vulnerability over the next 10 to 20 years is likely to be dominated by socioeconomic factors and legacy issues; c) even countries and sectors that stand to benefit from climate change are poorly positioned to do so; and d) the next decade offers a window of opportunity for ECA countries to make their development more resilient to climate change while reaping numerous co-benefits.